Grounding Islamic Education Transformation in Religious Moderation: Bridging the Policy-Practice Gap in Indonesia's Merdeka Curriculum - Nursani Awal Artha Nugraha; Agus Fakhruddin; Aldam Shaka Pradipta; Helmy Abdullah Helmy; Pitra Gosha Patriasya (Southeast Asian Journal of Islamic Education, 2026)
The policy-practice gap constitutes a persistent challenge in Indonesia's Islamic education transformation as two landmark policy reforms converge: the Merdeka Curriculum (2022) and Presidential Regulation on Religious Moderation (2023). Despite evident institutional commitments, implementation frequently remains superficial, constraining the effectiveness of digital technology integration. Religious moderation values internalization, pedagogical innovation, and curriculum reform across diverse Islamic educational institutions. This systematic review synthesizes empirical evidence from 55 peer-reviewed, Scopus-indexed studies (2020-2025) and uses the PRISMA 2020 protocol to identify strategic pathways to bridge this gap. Findings reveal that sustainable transformation requires cross-dimensional integration of digital technology, religious moderation, pedagogical innovation, and curriculum reform, with religious moderation operationalized through wasatiyyah values and dialogical methods, which emerge as a foundational anchor of the entire transformation framework. Teacher digital competency gaps and structural policy-practice misalignment constitute the most critical implementation barriers. The integrative conceptual model constructed demonstrates that transformative success depends on three strategic pillars: strong institutional leadership, sustained teacher capacity development, and coherent alignment between policy design and field implementation capacity. These findings offer evidence-based pathways for policymakers, practitioners, and researchers committed to designing sustainable, equitable, and empirically grounded Islamic education transformation within Indonesia's Merdeka Curriculum era.